1991
DOI: 10.1007/bf00016075
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of unstable RNA transcripts of insecticidal crystal protein genes of Bacillus thuringiensis in transgenic plants and electroporated protoplasts

Abstract: We have examined expression of several insecticidal crystal protein (ICP) genes of Bacillus thuringiensis in transgenic tobacco plants and electroporated carrot protoplasts. We determined that low levels of lepidopteran toxin cryIA(b) ICP gene expression in plants and electroporated carrot cells is due to RNA instability. We used a series of 3' deleted by cryIA(b) constructs directed by the cauliflower mosaic virus 35S promoter to demonstrate that this instability is minimally contained in the first 579 bases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(63 citation statements)
references
References 61 publications
2
60
1
Order By: Relevance
“…Some mRNAs in plants and yeast are thought to be destabilized because they include rare codons that cause the ribosome to stall during translation (Hoekemaet al, 1987;Murray et al, 1991). A comparison of PHYA mRNA codon usage to the average codon usage of 207 plant genes (Murray et al, 1991) indicated that PHYA mRNA contains a distribution of codons that closely fits the average plant codon usage distribution (data not shown), suggesting that PHYA mRNA is not destabilized by this mechanism.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Some mRNAs in plants and yeast are thought to be destabilized because they include rare codons that cause the ribosome to stall during translation (Hoekemaet al, 1987;Murray et al, 1991). A comparison of PHYA mRNA codon usage to the average codon usage of 207 plant genes (Murray et al, 1991) indicated that PHYA mRNA contains a distribution of codons that closely fits the average plant codon usage distribution (data not shown), suggesting that PHYA mRNA is not destabilized by this mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…A comparison of PHYA mRNA codon usage to the average codon usage of 207 plant genes (Murray et al, 1991) indicated that PHYA mRNA contains a distribution of codons that closely fits the average plant codon usage distribution (data not shown), suggesting that PHYA mRNA is not destabilized by this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of identifying the most effective ICP has been pointed out (32). Since native cry genes have poor coding capacity in plants (33), the cryIAc gene was duly reconstructed.…”
Section: Discussionmentioning
confidence: 99%
“…The wild type cry1Ab gene corresponded to the amino acid positions 29 to 618. According to the Northern blot analysis, the sequence of the 56 kDa protein obtained from the wild type cry1Ab gene might have been interrupted at the ATTTA sequences of 1.6 kb (Murray et al 1991) and not digested at the second trypsin cleavage site of the amino acids at positions 601 and 602. Survival pattern of H. armigera reared on the mcbttransformed lines was significantly different from that of the insects reared on the non-transformed control, when the expression level of Cry1Ab ICP in the mcbt-transformed lines exceeded 12.3 ng per 50 µg.…”
Section: Discussionmentioning
confidence: 99%
“…The low level of expression of the Bt gene in plants is due to mRNA instability (Ohme- Takagi et al 1993, Chen andShyu 1995), which mainly results from the presence of ATTTA sequences (Murray et al 1991, Van Aarssen et al 1995. Modification of the coding sequences successfully enhanced plant expression of Bt genes (Perlak et al 1990, Sutton et al 1992, Adang et al 1993, Koziel et al 1993.…”
Section: Introductionmentioning
confidence: 99%